2014
DOI: 10.15517/rgac.v0i50.15120
|View full text |Cite
|
Sign up to set email alerts
|

Mamíferos del Pleistoceno Terminal de la localidad de El Hatillo, Panamá

Abstract: Late Pleistocene mammals from the El Hatillo locality on the Azuero Peninsula in Panama, originally reported by C. L. Gazin in 1957, are documented here for the first time. The following taxa are present: Hoplophorinae?, Glyptotherium floridanum, Eremotherium laurillardi, Paramylodon harlani, Equus conversidens, Platygonus sp., Odocoileus sp., Mixotoxodon larensis and Cuvieronius hyodon. This is a characteristic assemblage of late Pleistocene mammals from Central America that is dominated by fossils of Eremoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…A mylodontid mandible from El Hatillo, Panama was initially identified as cf. Glossotherium tropicum [143] but has since been referred to Paramylodon harlani [144].…”
Section: Mylodontid Indetmentioning
confidence: 99%
“…A mylodontid mandible from El Hatillo, Panama was initially identified as cf. Glossotherium tropicum [143] but has since been referred to Paramylodon harlani [144].…”
Section: Mylodontid Indetmentioning
confidence: 99%
“…There are only a few records of mylodontinae sloths in Central America, including in Guatemala [44,45], Costa Rica [46], and Panama [47]. Generally, most records are reported simply as a mylodontid, but some specimens have been identified specifically as Paramylodon.…”
Section: Paramylodon Anatomy and Physiologymentioning
confidence: 99%
“…Despite this importance, until recently our knowledge of late Miocene biotas has been restricted to marine faunas such as the hyperdiverse, Gatun Formation, which preserves an excellent record of both invertebrates [1] and chondrichthyans [2]. In contrast to the marine record, up to now no terrestrial macrofossils have been reported in Panama from the time interval between the early Miocene of the Panama Canal localities [3] and the late Pleistocene of the Azuero Peninsula [4]. The apparent lack of terrestrial sedimentation, as evidenced by the paucity of outcrops during the late Miocene portion of this interval, likely resulted from the rapid uplift and consequent erosion during the formation of the isthmus [5].…”
Section: Introductionmentioning
confidence: 99%